Impact of sarcopenia and myosteatosis on survival outcomes for patients with head and neck cancer undergoing curative-intent treatment. Issue 3 (14th February 2023) - Ahern, Elizabeth; Brown, Teresa Ellen; Campbell, Louise; Hughes, Brett G. M.; Banks, Merrilyn; Lin, Charles Y.; Kenny, Lizbeth M.; Bauer, Judith
Abstract: Malnutrition and sarcopenia are prevalent in patients with head and neck squamous cell carcinoma (HNSCC). Pre-treatment sarcopenia and adverse oncological outcomes in this population are well described. The impact of myosteatosis and post-treatment sarcopenia is less well known. Patients with HNSCC ( n = 125) undergoing chemoradiotherapy, radiotherapy alone and/or surgery were assessed for sarcopenia and myosteatosis, using cross-sectional computed tomography (CT) imaging at the third lumbar (L3) vertebra, at baseline and 3 months post-treatment. Outcomes were overall survival (OS) at 12 months and 5 years post-treatment. One hundred and one participants had a CT scan evaluable at one or two time points, of which sixty-seven (66 %) participants were sarcopenic on at least one time point. Reduced muscle attenuation affected 93 % ( n = 92) pre-treatment compared with 97 % ( n = 90) post-treatment. Five-year OS favoured those without post-treatment sarcopenia (hazard ratio, HR 0·37, 95 % CI 0·16, 0·88, P = 0·06) and those without both post-treatment myosteatosis and sarcopenia (HR 0·33, 95 % CI 0·13, 0·83, P = 0·06). Overall, rates of myosteatosis were high at both pre- and post-treatment time points. Post-treatment sarcopenia was associated with worse 5-year OS, as was post-treatment sarcopenia in those who had myosteatosis. Post-treatment sarcopenia should be evaluated as an independent risk factor for decreased long-term survival post-treatment containing radiotherapy (RT) for HNSCC.